2015
DOI: 10.3390/nu7125497
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Zinc Deficiency Alters Chick Gut Microbiota Composition and Function

Abstract: Zinc (Zn) deficiency is a prevalent micronutrient insufficiency. Although the gut is a vital organ for Zn utilization, and Zn deficiency is associated with impaired intestinal permeability and a global decrease in gastrointestinal health, alterations in the gut microbial ecology of the host under conditions of Zn deficiency have yet to be studied. Using the broiler chicken (Gallus gallus) model, the aim of this study was to characterize distinct cecal microbiota shifts induced by chronic dietary Zn depletion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
188
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(204 citation statements)
references
References 93 publications
8
188
1
Order By: Relevance
“…51 Animal studies have indicated that zinc deficiency alters microbial function and composition. 52 Moreover, some ion channels, such as KCNN4, which share membrane transporter properties and roles with solute transporters, are activated by intracellular calcium and regulate Paneth cell secretion 53 with an impact on immune cell and epithelial cell function. 54 Therefore, we speculate that by disturbing the transmembrane domain of SLC39A8, Ala391Thr may alter zinc metabolism in functionally relevant cells, which might in turn affect innate and adaptive immunity, as well as the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…51 Animal studies have indicated that zinc deficiency alters microbial function and composition. 52 Moreover, some ion channels, such as KCNN4, which share membrane transporter properties and roles with solute transporters, are activated by intracellular calcium and regulate Paneth cell secretion 53 with an impact on immune cell and epithelial cell function. 54 Therefore, we speculate that by disturbing the transmembrane domain of SLC39A8, Ala391Thr may alter zinc metabolism in functionally relevant cells, which might in turn affect innate and adaptive immunity, as well as the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, zinc-associated bacterial alterations may occur at a lower taxonomic level than were measured here. In chickens, chronic zinc deficiency promoted a significant increase in Proteobacteria, which is a phylum that represented a major proportion of the fecal microbiota of dZD mice (23, 24). However, this phylum constituted a major proportion of the well-nourished profile of 46-d-old mice, increasing notably from 36 d old, and may, therefore, be part of the microbial aging process.…”
Section: Discussionmentioning
confidence: 99%
“…The Gallus gallus model was shown to exhibit the appropriate responses to Fe deficiency and that it can serve as a model for human Fe bioavailability. More specifically, it is a fast growing animal that is sensitive to dietary mineral deficiencies [60] and is very receptive to dietary manipulations [15,16,17,55,60,61,67,68,69,70,71]. There is also >85% homology between gene sequences of human and chicken intestinal divalent metal transporter 1 (DMT1, the major intestinal Fe transporter), duodenal cytochrome B (DcytB, Fe reductase), ZnT1 (a major intestinal Zn exporter) and Ferroportin (the major intestinal enterocyte Fe exporter), which are key proteins that are essential for Fe and Zn metabolism [72].…”
Section: Introductionmentioning
confidence: 99%